PEMIKIRAN PENDIDIKAN NYAI AHMAD DAHLAN DALAM MEMBERDAYAKAN PEREMPUAN - Fahmi Riady (Sekolah Tinggi Agama Islam Ma'had Ali Cirebon, 2019)
In the early of twentieth century, the women’s movement was considered debauch; however, Nyai Ahmad Dahlan fight it. She founded Sopo Tresno (later became Aisyiyah). She encouraged the women to know the social problem, and empowered them. Other, she founded hostel for women (internaat), that was her thought in empowering women were found. Nyai Ahmad Dahlan emphasized the importance of discipline, well mannered, knowledge, and skill for women. And of course their participation in society.